CHARACTERISTICS OF BODY LOTION PREPARATIONS WITH DIFFERENT CONCENTRATIONS OF RED SEAWEED Eucheuma spinosum - Mesang, Selni; Henggu, Krisman Umbu (Aurelia Journal, 2024)
Eucheuma spinosum seaweed is a species of seaweed that is quite abundant in East Sumba Regency, but its use is still limited. This seaweed is known to have a high carrageenan content and can be used as a stabilizer and emulsifier in cosmetic products, one of which is body lotion. This research examines different E. spinosum formulations (0%, 5%, 10%, 15%) on the characteristics of the body lotion produced. The research results show that the characteristics of body lotion have an average pH value ranging from 7.6-8.4, an IC50 value ranging from 259 ± 2.27 ppm to 454 ± 3.38 ppm, and does not meet antioxidant standards for cosmetic preparations. The homogeneity of body lotion still contains seaweed granules, which are not homogeneous. Different concentrations of E. spinosum did not significantly affect color, aroma, or texture. However, it affects absorption capacity.